Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus in long-term care facilities in eastern Taiwan - Hsin-Chi Tsai; Tung-Yi Huang; Jung-Sheng Chen; Wen-Jen Chen; Chong-Yen Lin; Bing-Mu Hsu (Tzu Chi Medical Journal)
Objective: The prevention of infections is crucial in long-term care programs. Investigations of the occurrence and sources of pathogens in long-term care facilities (LTCFs) are still lacking, especially in eastern Taiwan. In this study, we conducted a surveillance of two common pathogens, Acinetobacter baumannii (AB) and methicillin-resistant Staphylococcus aureus (MRSA), in LTCFs in Hualien. Materials and Methods: Pathogenic assays including isolation, identification, and antimicrobial susceptibility tests were conducted for AB and MRSA at LTCFs in Eastern Taiwan. Staphylococcal cassette chromosome mec typing assays were done to understand the relatedness of clonal strains of MRSA. Results: All AB-positive samples in the LTCFs were mainly from water-rich samples and were drug susceptible. Our data indicated that the AB strains from LTCFs were similar to those from Puzi River watersheds in Taiwan, which were not drug resistant to commonly used antibiotics. On the other hand, the drug resistance analysis of MRSA indicated that the genotypes from the LTCFs were similar to those from nearby hospitals. Eight strains of MRSA were isolated from four LTCFs, of which five were identified as hospital-acquired strains according to SSCmed typing assays. Conclusion: These findings suggest that MRSA in LTCFs might propagate from hospitals and could be transmitted between hospitals and LTCFs. Health authorities should be aware of this risk. The long-term follow-up of MRSA is recommended in local medical institutions as well as in LTCFs for correlative analysis.